2017
DOI: 10.3823/2416
|View full text |Cite
|
Sign up to set email alerts
|

Timed Up And Go Risk Predictor Of Falls In Elderly People Residing In The Community?

Abstract: Objective: evaluate the risk of falls of elderly people residing in a community in northeastern Brazil using the "Timed up and go". Method:Descriptive study, with a quantitative approach, performed with elderly people residing in a community. The collected data related to the sociodemographic and economic characteristics of episodes of falls in the last two years, regular practice of physical exercise and complaint of pain at the time of the interview; and, at last, the application of the "Timed up and Go" tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Além da necessidade de atenção com esse tema, pois a queda é um acontecimento que acomete muitos idosos, é muito importante se avaliar o risco de quedas para se tomar as medidas necessárias. (Guerra, et al, 2017;Rodrigues, et al, 2017).…”
Section: Discussionunclassified
“…Além da necessidade de atenção com esse tema, pois a queda é um acontecimento que acomete muitos idosos, é muito importante se avaliar o risco de quedas para se tomar as medidas necessárias. (Guerra, et al, 2017;Rodrigues, et al, 2017).…”
Section: Discussionunclassified
“…O fato de a expectativa de vida da população estudada ser semelhante à média nacional leva a crer que as taxas de déficit de equilíbrio em idosos sejam, também, semelhantes. Na presente amostra (média de idade de 71,1 ± 7,8), a idade se relacionou diretamente com o declínio do equilíbrio, assim como ocorreu em outras pesquisas que se propuseram a estudar essa relação (Rodrigues, et al, 2017;Pavanate, et al, 2018). Vale lembrar que indivíduos muito fragilizados e incapazes de executar o TUG (possivelmente indivíduos de mais idade) preencheram critério de exclusão, logo, é possível que a média real de idade dos pacientes com déficit de equilíbrio seja ligeiramente maior.…”
Section: Discussionunclassified
“…Also, we found that as the elderly age increases, the risk of fall also increases which is compatible with previous studies. [ 6 7 9 15 ] As age increases, the risk of age-related comorbidities increases as well. The presence of the underlying disease is one of the most important risk factors for falling.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] It is recommended especially by US Preventive Services Task Force and The American Geriatrics Society and British Geriatrics Society that fall risk screening be done in the elderly by the healthcare provider so that preventive interventions can be made. [ 5 6 7 8 ]…”
Section: Introductionmentioning
confidence: 99%